2020
DOI: 10.11591/edulearn.v14i3.14553
|View full text |Cite
|
Sign up to set email alerts
|

Quality of blended learning as perceived by Arab Open University students

Abstract: The primary goal of this research was to investigate AOU students' conceptions of the quality of online experience through the learning management system in supporting their classroom tutorials. A 32-item questionnaire was administered to a randomly selected sample (205) of Elementary Education students at the AOU Jordan Branch. On one hand, the results showed that the objectives of the courses were very clear to students, online materials on the learning management system were interesting and supported to cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Previous studies have confirmed that students upload and download resources through learning management systems and take part in discussion boards (Hu et al, 2019;Mpungose & Khoza, 2020). However, there was no discernible difference in the amount of time students spent utilizing the application, the number of documents uploaded and downloaded, or the frequency of logging in relation to their learning outcomes (Hwang, 2020;Mwalumbwe & Mtebe, 2017;Tawalbeh, 2020). This circumstance most likely arises from students' poor selflearning (Hughes et al, 2018).…”
Section: Discussionmentioning
confidence: 92%
“…Previous studies have confirmed that students upload and download resources through learning management systems and take part in discussion boards (Hu et al, 2019;Mpungose & Khoza, 2020). However, there was no discernible difference in the amount of time students spent utilizing the application, the number of documents uploaded and downloaded, or the frequency of logging in relation to their learning outcomes (Hwang, 2020;Mwalumbwe & Mtebe, 2017;Tawalbeh, 2020). This circumstance most likely arises from students' poor selflearning (Hughes et al, 2018).…”
Section: Discussionmentioning
confidence: 92%